Error Analysis on Grammar in Writing News Item Text Made by The First Year Students of MA Syekh Subakir Nglegok Blitar - Ahmad Saifudin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2019)
This study was aimed at finding out the errors of news item text made by the tenth grade students of MA Syekh Subakir Nglegok Blitar. This study was conducted by using qualitative approach. Sukardi (2003:86) stated in qualitative research, the analysis was done to arrange and group the data in terms of facts, words, sentences, arguments or reasons. Specifically, the design of this study was qualitative research. The subjects of the study covered the tenth grade students of MA Syekh Subakir Nglegok. The researcher took the tenth grades because the researcher used news item text in his research. After getting the compositions, the researcher made three steps first; Rresearcher read each of the 10 writing carefully. Then, the researcher analyzed the data by using the analysis tools. Second the researcher continued to the next step of analysis. It was classification of the data; it was classified into error types and gave a clear description of the study. Afterwards, the identified errors were rewritten in separate list. The last the errors was classified based on the surface strategy taxonomy. The errors were counted each type. In this study, the instrument used was the result of writing test. It was about news item text. It was taken from their own teacher. After the data was collected, the data processing procedure was carried out. The reasearcher identified the errors. Then the researcher described by reconstructed sentences with the original one, the correct grammar and classify them based on the categories of errors analysis. Getting the data from the authentic results, it can be answered the statement problem and taken some conclusions that, mostly, the English learners still have difficulties in apprehending English grammar as a foreign language.